METAVERSE AND LANGUAGE LEARNING: ALIGNING MODERN TECHNOLOGIES WITH CONTEMPORARY CHANGES - نبيلة نبيل طوخي قنديل (“ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI” MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2024)
The world has recently witnessed a variety of contemporary changes in information, knowledge, and culture, leading students to grow weary of traditional teaching methods. The Metaverse initiative is based on creating three-dimensional environments that blend reality and imagination using clear and safe tools. It integrates the real world with virtual reality (VR), augmented reality (AR), mixed reality (MR), 3D environments, and artificial intelligence (AI) technologies. This is achieved by building virtual spaces, providing special glasses, and applying this technology in schools and universities for diverse students. Enjoyment and excitement are among the most prominent features of this strategy, as both students and teachers experience a three-dimensional virtual reality that aligns with the characteristics of Generation Z, which relies on technology and AI. Moreover, this technology encourages self-learning and offers a space for education under unusual circumstances, such as pandemics. The Metaverse is considered an innovative solution in modern educational strategies, providing interactive virtual environments that facilitate engagement between teachers and students. It addresses educational needs by simulating markets, hotels, streets, schools, and universities and offering a great opportunity to interact with native speakers, thereby improving listening and speaking skills while increasing student motivation. However, its high cost and certain ethical concerns pose challenges. Despite these issues, the Metaverse has demonstrated positive results in enhancing listening and speaking skills in numerous studies, encouraging further implementation and efforts to overcome obstacles. This highlights its significant impact on education in addressing contemporary changes.